2013
DOI: 10.1161/strokeaha.111.000798
|View full text |Cite
|
Sign up to set email alerts
|

Urgent Best Medical Therapy May Obviate the Need for Urgent Surgery in Patients With Symptomatic Carotid Stenosis

Abstract: Background and Purpose-The purpose of this study was to analyze the 30-day outcome after introduction of a rapid carotid endarterectomy (CEA) program. Reasons for delay in CEA and the incidence of early recurrence neurological symptoms were recorded. Methods-This is a prospective population-based study of delays to CEA and 30-day outcome in patients with symptomatic carotid stenosis. Neurological recurrence (NR) rate was determined after initiation of urgent best medical treatment (loading dose aspirin/clopido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 21 publications
1
22
0
1
Order By: Relevance
“…This is based on the published perioperative stroke or death rate of between 6% in more recent studies and 6.7% in NASCET [1, 28]. However, given that both medical therapy and revascularization procedures have made significant advances since that time with lower event rates seen in population-based studies of both therapies, several experts have called for new randomized trials to reassess this clinical question, particularly among subsets of patients who were previously shown to benefit less from CEA [29, 30]. These subgroups have been identified in several analyses, including a pooled analysis of patients with greater than 50% stenosis from prior CEA trials.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…This is based on the published perioperative stroke or death rate of between 6% in more recent studies and 6.7% in NASCET [1, 28]. However, given that both medical therapy and revascularization procedures have made significant advances since that time with lower event rates seen in population-based studies of both therapies, several experts have called for new randomized trials to reassess this clinical question, particularly among subsets of patients who were previously shown to benefit less from CEA [29, 30]. These subgroups have been identified in several analyses, including a pooled analysis of patients with greater than 50% stenosis from prior CEA trials.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Furthermore, symptomatic carotid stenoses must be promptly identified, that is, directly upon the patient's admission, in order to decide upon an intervention as early as possible when planning future treatment. The combination of B-image sonographic plaque characterization to assess embolism risk and Doppler sonographic estimation of hemodynamic changes (by measuring the collateral circulation) explains the pathomechanism of symptomatic internal carotid artery stenoses and can determine early medical secondary stroke prevention [9][10][11].…”
Section: Ultrasound Findings During the Acute Phase Of The Cerebral Imentioning
confidence: 99%
“…1 However, there are concerns that interventions performed < 48 h after symptom onset are associated with increased procedural risks (that may offset potential benefits), 2 and that a more aggressive approach towards implementing "best medical therapy" (BMT) may avoid the need for urgent CEA after the onset of transient ischaemic attack (TIA) or minor ischaemic stroke. 3 In the latest SwedVasc report, 4 Kragsterman et al attribute the significant decline in recurrent cerebrovascular events (stroke, TIA, retinal events), observed between the onset of the index symptom and 30 days post-CEA (31% in 2008e09, down to 21% in 2014e15), to a significant reduction in the median delay from index symptom to undergoing CEA (13 days in 2008e09), down to 7 days in 2014e15.The reduction in surgical delays was achieved without an increase in the 30 day rate of death/stroke after CEA. 4 In the current SwedVasc study, it was not possible to evaluate the potentially important contribution of rapid implementation of BMT between onset of symptoms and undergoing expedited CEA.…”
mentioning
confidence: 99%
“…However, prospective, observational studies have reported that rapid implementation of BMT (especially dual antiplatelet therapy [DAPT] and statin therapy) significantly reduces spontaneous embolisation and early, recurrent cerebrovascular events. 2,3,5,6 So, is it preferable to start BMT as soon as possible and then perform CEA "within 30 days in neurologically stable patients", as advocated by Shahidi et al, 3 or do the benefits of rapidly implemented BMT now enable the surgeon to avoid performing CEA in the first 48 h after onset of symptoms and then plan for expedited CEA shortly thereafter? This is probably Swedish policy following a 2012 audit.…”
mentioning
confidence: 99%